Robust Strong Structural Controllability of Complex Power Systems - Sun, Yunhe; Yang, Dongsheng; Gao, Xiaoting; Qin , Jia (Frontiers in Energy Research, 2022)
Ensuring the control of power systems is crucial for the safe operation. This paper analyses the robust controllability of complex power systems from the structural sight. Stressing the dominant role of generators in the control of power systems, we propose three kinds of controllable networks by generator nodes. Additionally, the satisfied conditions and the relevant proof of zero forcing set in the controllable networks by generator nodes and extra nodes are given. Besides, the satisfied conditions and the relevant proofs of the largest set of removable edges that no-effect on the strong structural controllability in three kinds of controllable networks by generator nodes are proposed. Finally, the robustness of strong structural controllability of IEEE 39 bus system has been analyzed. The zero forcing set and the largest set of removable edges of IEEE 39 bus system are provided.